Loss of the dermis zinc transporter ZIP13 promotes the mildness of fibrosarcoma by inhibiting autophagy - Lee, Mi Gi; Choi, Min Ah; Chae, Sehyun; Kang, Mi Ae; Jo, Hantae; Baek, Jin myoung; In, Kyu Ree; Park, Hyein; Heo, Hyojin; Jang, Dongmin; Brito, Sofia; Kim, Sung Tae; et al. (Scientific Reports, 2019)
Fibrosarcoma is a skin tumor that is frequently observed in humans, dogs, and cats. Despite unsightly appearance, studies on fibrosarcoma have not significantly progressed, due to a relatively mild tumor severity and a lower incidence than that of other epithelial tumors. Here, we focused on the role of a recently-found dermis zinc transporter, ZIP13, in fibrosarcoma progression. We generated two transformed cell lines from wild-type and ZIP13-KO mice-derived dermal fibroblasts by stably expressing the Simian Virus (SV) 40-T antigen. The ZIP13−/− cell line exhibited an impairment in autophagy, followed by hypersensitivity to nutrient deficiency. The autophagy impairment in the ZIP13−/− cell line was due to the low expression of LC3 gene and protein, and was restored by the DNA demethylating agent, 5-aza-2’-deoxycytidine (5-aza) treatment. Moreover, the DNA methyltransferase activity was significantly increased in the ZIP13−/− cell line, indicating the disturbance of epigenetic regulations. Autophagy inhibitors effectively inhibited the growth of fibrosarcoma with relatively minor damages to normal cells in xenograft assay. Our data show that proper control over autophagy and zinc homeostasis could allow for the development of a new therapeutic strategy to treat fibrosarcoma.
Keywords: Animals; Autophagy; Azacitidine; Cation Transport Proteins; Cell Death; Cell Line; Dermis; Disease Models, Animal; DNA (Cytosine-5-)-Methyltransferases; Down-Regulation; Ethylenediamines; Fibrosarcoma; Humans; Mice, Knockout; Microtubule-Associated Proteins; Zinc